2012
DOI: 10.1002/etc.1791
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane integrity and internalization of ingested TiO2 nanoparticles by digestive gland cells of a terrestrial isopod

Abstract: The present study was motivated by the paucity of reports on cellular internalization of ingested titanium dioxide (TiO(2)) nanoparticles (nano-TiO(2)). The model invertebrate (Porcellio scaber, Isopoda, Crustacea) was exposed to food dosed with nano-TiO(2) containing 100, 1,000, 3,000, or 5,000 µg nano-TiO(2) per gram of food. After 14 d of exposure, the amount of Ti in the entire body was analyzed by inductively coupled plasma-mass spectrometry, and elemental analyses of tissue cross sections were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Newer visualisation and quantification techniques such as sedimentation field flow fractionation analysis (Deering et al, 2008) or particle-inducd x-ray emission in combination with inductively coupled mass spectrometry (Novak et al, 2012) may be helpful in this arena. The importance of a non-NP control is critical in such studies, however, as demonstrated by the finding in an ex vivo digestion model that dosing with ionic silver, in the form of AgNO 3 , resulted in NP formation following exposure to low pH and chloride ions (Walczak et al, 2012).…”
Section: Discussion: Relevant Factors For Np Ingestion Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer visualisation and quantification techniques such as sedimentation field flow fractionation analysis (Deering et al, 2008) or particle-inducd x-ray emission in combination with inductively coupled mass spectrometry (Novak et al, 2012) may be helpful in this arena. The importance of a non-NP control is critical in such studies, however, as demonstrated by the finding in an ex vivo digestion model that dosing with ionic silver, in the form of AgNO 3 , resulted in NP formation following exposure to low pH and chloride ions (Walczak et al, 2012).…”
Section: Discussion: Relevant Factors For Np Ingestion Studiesmentioning
confidence: 99%
“…Better methods of determining the delivered dose at the cellular or organ level for in vivo studies would assist in rational comparison with in vitro results [Deering et al, (2008), #245; Novak et al, (2012), #265]. Additionally, improved in vivo methods of measuring more subtle functional parameters with respect to metabolism, immune function, oxidative stress, or other physiological aspects would be helpful.…”
Section: Discussion: Relevant Factors For Np Ingestion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…approximately one cell diameter). Despite less than optimal preservation, cryostat sections with thicknesses ranging from 10 to 100 lm are acceptable for a range of low-and intermediate-resolution applications in animals Morgan et al 2013;Novak et al 2012) and plants (Tian et al 2010). For high resolution applications such as TEM, the well-frozen surface layer can be significantly deepened to around 200 lm in fresh tissues by hyperbaric freezing or alternatively the ice damage can be eliminated by pretreating specimens typically by mild aldehyde fixation followed by infusion with a cryo-protectant such as sucrose.…”
Section: Sample Preparation For Imaging/analysis: Common Considerationsmentioning
confidence: 99%
“…As a result, anatase is widely used in self-cleaning glass and solar panels, as well as water purication membrane components. 15,16 In vitro, disruption of eukaryotic cell membranes by TiO 2 NPs was described. The toxicity of these materials needs therefore to be studied.…”
Section: Introductionmentioning
confidence: 99%